Analisis dan Desain Pengembangan Bahan Ajar Berbasis Mind Mapping Pada Mata Pelajaran SKI di Madrasah Tsanawiyah Negeri 1 Ponorogo - Faida Halifah (Social Science Academic, 2024)
This research aims to understand the analysis and design of developing mind mapping-based teaching materials in the subject of Islamic cultural history. This research uses the research and development method using the Mindomo application using the ADDIE development model, where in this research the researcher will only use two steps, analysis and design. The research population was class VII students of Madrasah Tsanawiyah Negeri 1 Ponorogo. The results of this research show that mind mapping-based teaching materials can make narrative learning more concise, making it easier for teachers to teach and increasing students' learning motivation.